The Role of Lifestyle as a Determinant of Consumers’ Purchase Decisions on Sukarara Woven Products - Ramdani, Rizal; Bukran, Bukran (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
In the current era of globalization, the dynamics of cultural exchange and technological advancement have profoundly transformed consumer behavior and market orientation. Consumption patterns have shifted from a primarily functional focus toward the fulfillment of psychological and social needs, where lifestyle has become a key determinant of purchasing decisions for traditional cultural products. This study aims to examine the influence of consumer lifestyle, consisting of the dimensions of activities, interests, and opinions, on purchasing decisions for Sukarara woven products. A quantitative research design with a descriptive approach was employed, and data were collected from 150 purposively selected respondents using a structured questionnaire with a five point Likert scale. The data were analyzed using multiple linear regression through SPSS software to assess the contribution of each lifestyle dimension. The results indicate that all three dimensions have a significant and positive effect on purchasing decisions, with interests exerting the strongest influence, followed by activities and opinions. These findings demonstrate that modern consumers evaluate traditional products not only in terms of utility but also through symbolic meaning, aesthetic value, and expressions of self identity. The study emphasizes the importance of developing marketing strategies that enhance cultural relevance, diversify product usage, and strengthen value perceptions to sustain and promote Indonesia’s traditional weaving industry in the global market.